2021
DOI: 10.1007/s10854-021-05510-8
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of polarity reversion from Al(Ga)-polar to N-polar for AlGaN film on AlN seeding layer grown by a novel flow‐modulation technology

Abstract: N-polar AlGaN epi-layer was realized on AlN seeding layer grown with a novel flow-modulation method. The polarity reversion from Al(Ga)-polar to N-polar for AlGaN/AlN films was confirmed by KOH etching and subsequent observation with optical microscope as well as high-resolution X-ray diffraction (HR-XRD) measurement. In particular, the dependence of crystalline quality and defect size in the N-polar AlGaN epi-layers on the Ⅴ/Ⅲ ratio was investigated with HR-XRD and scanning electron microscopy (SEM). It was f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It should be noted that that the formation of N-polar islands occurred only near the liquid surface (Figure 5b,d), and one possible reason is the N−Al ratio: Zhang et al 34 and Keller et al 35 reported the synthesis of N-polar AlN crystals with high N− Al ratios using metal−organic chemical vapor deposition (MOCVD). In this work, the N−Al ratio is higher than that in other regions due to the adequate nitrogen supply at the N 2 -flux interface, causing the formation of N-polar AlN islands near the liquid level.…”
Section: Effect Of Polarity On Alnmentioning
confidence: 99%
“…It should be noted that that the formation of N-polar islands occurred only near the liquid surface (Figure 5b,d), and one possible reason is the N−Al ratio: Zhang et al 34 and Keller et al 35 reported the synthesis of N-polar AlN crystals with high N− Al ratios using metal−organic chemical vapor deposition (MOCVD). In this work, the N−Al ratio is higher than that in other regions due to the adequate nitrogen supply at the N 2 -flux interface, causing the formation of N-polar AlN islands near the liquid level.…”
Section: Effect Of Polarity On Alnmentioning
confidence: 99%